Deep Vein Thromboses in Injecting Drug Users: Meanings, Bodily Experiences, and Stigma. (September 2019) - Cornford, Charles; Fraser, Lorraine; Wright, Nat
Deep vein thromboses (DVTs) are common sequelae of injecting drugs into the groin. We explored meanings and experiences of DVTs in a group of 19 patients from the North East of England with a DVT and in treatment for opioid use. We report three themes: (a) DVT meaning making, (b) embodied experience, and (c) Stigma. Patients attributed DVTs to groin injecting, though thought other factors were also partially responsible. Medication performed both treatment and preventive functions. The most pertinent worry was amputation. Patients recognized stopping injecting as important, but it did not necessarily occur. Stigma resulted in delayed admission to hospital and feelings of isolation; support groups might alleviate the latter. Although groin injecting was undertaken partly to avoid the censure of being a drug user, ironically, a DVT led to long-standing stigmata that were discrediting signs of that exact status.